2018
DOI: 10.1155/2018/6250941
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Mechanical Properties in Polypropylene‐ and Glass‐Fibre‐Reinforced Peach Shell Lightweight Concrete

Abstract: e use of the polypropylene fibre and glass fibre with different volume fractions to improve the mechanical properties of peach shell lightweight concrete was investigated in this study. e volume fractions of 0.25%, 0.50%, and 0.75% were used for each fibre.e results showed that, as the polypropylene fibre and glass fibre were added into peach shell concrete, the density was reduced by up to 6.1% and the compressive strength, splitting tensile strength, and flexural strength were increased by 19.1%, 54.3%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
4
10
0
Order By: Relevance
“…e addition of PP fibers resulted in an increased flexure strength. Similar results were obtained and reported in previous studies [35][36][37] in which flexure strength of the mortar specimens increased with the inclusion of fibers. Daneti et al [35] have reported in their study that an increment of 25% in the flexure tensile strength of the foamed concrete specimens was observed for 2% fiber addition.…”
Section: Flexure Strength Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…e addition of PP fibers resulted in an increased flexure strength. Similar results were obtained and reported in previous studies [35][36][37] in which flexure strength of the mortar specimens increased with the inclusion of fibers. Daneti et al [35] have reported in their study that an increment of 25% in the flexure tensile strength of the foamed concrete specimens was observed for 2% fiber addition.…”
Section: Flexure Strength Figuresupporting
confidence: 92%
“…e increase in the tensile strength due to the addition of PP fibers has been previously reported. For example, the results of the study conducted by Wu et al [37] reveal that the splitting tensile strength of the specimens increased by 10-37% for PP fiber addition of 0.25-0.75% (volume fraction). e tensile stress transferred to the fibers precludes the propagation of microcracks, thus, amplify the splitting tensile strength [38].…”
Section: Indirect Tensile Strengthmentioning
confidence: 99%
“…12. When the ASC without any fibres was subjected to tension, cracks directly penetrated through the concrete matrix and concrete was severely damaged, which was considered as brittle failure [54]. Moreover, most of the AS aggregate on either side of the crack was broken under the tensile stress due to the low strength of the AS.…”
Section: Flexural Strengthmentioning
confidence: 99%
“…Wang et al [ 17 ] studied the reinforcement effect of glass fiber and carbon fiber on the mechanical properties of fiber reinforced polymer concrete through experiments. Wu et al [ 18 ] experimented and studied the effects of polypropylene fiber and glass fiber with different volume fractions on the mechanical properties of peach shell lightweight concrete and proved the enhancement effect of two kinds of fiber mixing on the mechanical properties of the concrete. Noh et al [ 19 ] conducted an experimental study on the engineering properties of carbon fiber and glass fiber reinforced recycled polymer concrete.…”
Section: Introductionmentioning
confidence: 99%